2017
DOI: 10.18535/ijsrm/v5i11.04
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Psychological Well-Being of Women Working in Southern Railways Tiruchirappalli

Abstract: Mental health is the foundation for well-being and effective functioning for an individual and for a community and that of women is important both for their own health and for the well-being of their children and families. Different factors have significant influence on the psychological well-being, like poor nutrition, diseases, injuries and severe pain in body part etc, which can contribute to well-being issues and psychological distress. Working women statistics, women suffer high levels of physical, sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It showed that 56 women working in southern railways, Tiruchirappalli had moderate level of marital satisfaction. 8 Stress in pregnancy is common and impacts negatively on women, infants and families. 9 Pregnancy and breastfeeding are factors that lead to special situations for females in the workplace and marital satisfaction is an index of psychological health that is affected by working.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that 56 women working in southern railways, Tiruchirappalli had moderate level of marital satisfaction. 8 Stress in pregnancy is common and impacts negatively on women, infants and families. 9 Pregnancy and breastfeeding are factors that lead to special situations for females in the workplace and marital satisfaction is an index of psychological health that is affected by working.…”
Section: Introductionmentioning
confidence: 99%